High levels of HIV drug resistance among adults failing second-line antiretroviral therapy in Namibia. Issue 37 (11th September 2020) - Jordan, Michael R.; Hamunime, Ndapewa; Bikinesi, Leonard; Sawadogo, Souleymane; Agolory, Simon; Shiningavamwe, Andreas N.; Negussie, Taffa; Fisher-Walker, Christa L.; Raizes, Elliot G.; Mutenda, Nicholus; Hunter, Christian J.; Dean, Natalie; et al.
Abstract : Abstract: To support optimal third-line antiretroviral therapy (ART) selection in Namibia, we investigated the prevalence of HIV drug resistance (HIVDR) at time of failure of second-line ART. A cross-sectional study was conducted between August 2016 and February 2017. HIV-infected people ≥15 years of age with confirmed virological failure while receiving ritonavir-boosted protease inhibitor (PI/r)-based second-line ART were identified at 15 high-volume ART clinics representing over >70% of the total population receiving second-line ART. HIVDR genotyping of dried blood spots obtained from these individuals was performed using standard population sequencing methods. The Stanford HIVDR algorithm was used to identify sequences with predicted resistance; genotypic susceptibility scores for potential third-line regimens were calculated. Two hundred thirty-eight individuals were enrolled; 57.6% were female. The median age and duration on PI/r-based ART at time of enrolment were 37 years and 3.46 years, respectively. 97.5% received lopinavir/ritonavir-based regimens. The prevalence of nucleoside reverse transcriptase inhibitor (NRTI), non-nucleoside reverse transcriptase inhibitor (NNRTI), and PI/r resistance was 50.6%, 63.1%, and 13.1%, respectively. No significant association was observed between HIVDR prevalence and age or sex. This study demonstrates high levels of NRTI and NNRTI resistance and moderate levels of PI resistance in people receiving PI/r-based second-line ART in Namibia. Findings underscore the need for objective and inexpensive measures of adherence to identify those in need of intensive adherence counselling, routine viral load monitoring to promptly detect virological failure, and HIVDR genotyping to optimize selection of third-line drugs in Namibia.